The role of social support and self-regulation on work readiness among students in vocational high school - Fatwa Tentama; Eva Riyansha Riskiyana (International Journal of Evaluation and Research in Education (IJERE), 2020)
Work readiness is an important factor that can determine the quality of prospective graduates and vocational high schools as one of the educational institutions that prepare human resources to need to pay attention to factors that can improve work readiness. This study aimed to empirically examine how social support and self-regulation influence the work readiness of vocational High School students. The population in this study was all students of grade XII in Vocational High School Muhammadiyah 1 Yogyakarta (a vocational high school), totaling 170 students, and the sample of this study was 111 students. The sampling technique used was randomized sampling using cluster random sampling technique. The data were collected with the work readiness scale, social support scale, and self-regulation scale. The data were then analyzed with multiple linear regression techniques. There was a very significant correlation between social support and selfregulation and they simultaneously influence work readiness (r = 0.490, p = 0.000). There was a very significant correlation between social support and work readiness (r = 0.344, p = 0.000). There is a very significant correlation between self-regulation and work readiness (r = 0.490, p = 0.000). Selfregulation plays dominant role in shaping work readiness.